Urgensi Analisis Pertanggungjawaban Hukum Terhadap Pelaku Kejahatan Dengan Kepribadian Ganda (Dissociative Identity Disorder) - Khoirun Nisa; Abraham Ferry Rosando (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study discusses the urgency of analyzing criminal liability for perpetrators of crimes with multiple personalities or Dissociative Identity Disorder (DID), a mental disorder that causes an individual to have more than one identity that can take over consciousness. The presence of this disorder raises legal issues regarding the perpetrator's ability to understand and control their actions, which is an absolute requirement for criminal liability in Indonesian criminal law. This study aims to determine and understand the urgency of analyzing legal liability for perpetrators of crimes with DID and provide recommendations regarding the form of regulation that should be applied.The research method used is a juridicalnormative approach by analyzing the provisions of the Criminal Code, Criminal procedure Code, Health Law, as well as legal and forensic psychiatric literature. The study's findings show that DID may affect the degree of the offender's guilt,particularly if the criminal's personality is not under the main identity, so that the perpetrator loses the ability to take responsibility. Therefore, the involvement of forensic psychiatrists is very important in determining the perpetrator's mentalt Satus at the time of the occurrence. This research advises the introduction of Specific laws that control the examination mechanism and standards for assessing the ability to take responsibility for people with DID, including rehabilitation procedures and community protection. Thus, it is hoped that these regulations willr Create legal certainty, substantive justice, and balanced protection for perrpetrators, victims, and the community.